2021
DOI: 10.1155/2021/9953554
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Deformation Law of Inner Waste Dump Slope in an Open‐Pit Coal Mine: A Case Study in Southeast Inner Mongolia of China

Abstract: The settlement and deformation of an open-pit mine waste dump were investigated by using field monitoring and numerical methods. The creep parameters of fine soil sand in the dump fill were inverted using the steady Burgers creep model, and FLAC3D software was used to simulate the dumping soil construction and development program. The results show that the settlement displacement of the dump increases with the time of dumping soil and tends to be stable after 4 years. In the creep attenuation stage of the cree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…In studies [25][26][27][28], researchers have used numerical modeling and simulation techniques to study the internal dump slope stability. Empirical and experimental studies of the internal dump stability are presented in [29,30]. Several researchers have proposed and evaluated stability analysis and internal dump design methods [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…In studies [25][26][27][28], researchers have used numerical modeling and simulation techniques to study the internal dump slope stability. Empirical and experimental studies of the internal dump stability are presented in [29,30]. Several researchers have proposed and evaluated stability analysis and internal dump design methods [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Chen and Zhang [14] studied the compression response of space variable rock columns with three-dimensional random fields. Cao et al [15,16] studied the settlement and deformation of an open-pit mine dump by combining field monitoring data and numerical simulations. Zhang et al [17] analyzed the anchor cable monitoring in the Nanfen open-pit mine and revealed the failure process of a bedding rock landslide and the stress evolution characteristics of negative Poisson's ratio (NPR) cables.…”
Section: Introductionmentioning
confidence: 99%
“…Slope failure is an inevitable aspect of economic mine slope design in the mining industry (Neil et al, 2020); large landslides or floor heaves have occurred at the south dump of the Antaibao Openpit Mine, the east dump of the Pingshuo Opencast Mine, the external waste dump at the "South Field" lignite mine, Northern Greece, the Jianshan dump of the Lanjian Iron Mine, etc. due to insufficient bearing capacity of foundations (Steiakakis et al, 2009;Cao et al, 2021;, which is a serious threat to mine safety and sustained operation. Hence, it is necessary to systematically study the bearing capacity of the foundation to ensure the safety and stability of the waste dump (Zhang et al, 2011;Chakraborty 2013;Park et al, 2017).…”
Section: Introductionmentioning
confidence: 99%